Pengaruh Pijat Oksitosin terhadap Kelancaran Produksi ASI pada Ibu Post Partum di Klinik Umum dan Rumah Bersalin Amanda Oku Timur: The Influence of Oxytocin Massage on The Efectiveness of Breast Milk Production in Post Pasrtum Mothers at The General Clicic and Delivery House Off Amanda Oku Timur - Oni Elena; Moneca Diah Listiyaningsih (Journal of Holistics and Health Sciences (JHHS), 2023)
Breast milk is the best food because it contains all the nutrients in the ideal amount and composition needed by babies. Unsmooth milk production on the first day of delivery can be caused by a lack of stimulation of the hormone oxytocin which plays a very important role in milk production. At the research site, the efforts made to expedite breast milk production were only giving breast milk facilitating drugs, non-pharmacological efforts to expedite breast milk production, one of which was oxytocin massage, had never been given so that this encouraged mothers to meet their baby's needs by giving formula milk because some mothers do not like to drink drug.To determine the effect of oxytocin massage on the smooth production of breast milk in post partum mothers at the Amanda Oku Timur General Clinic and Maternity Hospital. This study used a Quasi-Experimental method with a pre-experimental approach, namely one group pretest and posttest design. The population in this study were all post partum mothers as many as 30 respondents in June. The sample in this study was part of the total population of 15 respondents 2 days post partum mothers who met predetermined criteria. The sampling technique used purposive sampling, observation sheet data collection instruments, statistical tests used the Wilcoxon Matched Pairs Signed Test.Based on the results of statistical tests using the Wilcoxon test, it was found that the p-value on the frequency of breastfeeding babies and the frequency of infant BAK was 0.001, at α 5%, which means the p-value < α. So it can be significant that there is an effect of oxytocin massage on the smooth production of breast milk in post partum mothers at the Amanda Oku Timur General Clinic and Maternity Hospital. Based on the analysis that has been done, oxytocin massage is effective for smooth milk production. There is an effect of oxytocin massage on the smooth production of breast milk, because there is a significant difference between the smooth production of breast milk before and after treatment. It is suggested that health workers, especially midwives, can socialize the benefits of oxytocin massage as an effort to expedite milk production.   ABSTRAK ASI merupakan makanan terbaik karena mengandung zat gizi dengan jumlah dan komposisi ideal yang dibutuhkan bayi. Ketidaklancaran produksi ASI hari pertama melahirkan dapat disebabkan kurangnya rangsangan hormone oksitosin yang sangat berperan dalam produksi ASI. Ditempat penelitian upaya yang diberikan untuk melancarkan produksi ASI hanya memberikan obat pelancar ASI, Upaya nonfarmakologis untuk melancarkan produksi ASI salah satunya pijat oksitosin belum pernah diberikan. Tujuan penelitian ini untuk mengetahui pengaruh pijat oksitosin terhadap kelancaran produksi ASI pada ibu post partum di Klinik Umum dan Rumah Bersalin Amanda Oku Timur. Penelitian ini menggunakan jenis metode Quasi Eksperimen dengan pendekatan pre eksperiment yaitu one group pretest dan posttest design. Populasi dalam penelitian ini seluruh ibu post partum 30 responden pada bulan Juni. Sampel pada penelitian ini 15 responden ibu post partum 2 hari yang memenuhi criteria. Teknik pengambilan sampel purposive sampling, instrumen pengumpulan data lembar observasi, uji statistic yang digunakan Wilcoxon Matched Pairs Signed Test.Berdasarkan hasil uji statistic menggunakan uji Wilcoxon didapatkan p-value pada frekuensi menyusui bayi dan frekuensi BAK bayi sebesar 0,001, pada α 5% yang artinya p-value < α. Sehingga dapat disimpulkan bahwa ada pengaruh pijat oksitosin terhadap kelancaran produksi ASI pada ibu post partum di Klinik Umum dan Rumah Bersalin Amanda Oku Timur. Berdasarkan hasil penelitian menunjukkan pijat oksitosin efektif untuk kelancaran produksi ASI. Ada pengaruh pijat oksitosin terhadap kelancaran produksi ASI, ada perbedaan yang signifikan antara kelancaran produksi ASI sebelum dan setelah perlakuan. Saran agar petugas kesehatan khususnya bidan dapat mensosialisasikan manfaat pijat oksitosin sebagai upaya melancarkan produksi ASI.